Effective cloud optical depth for overcast conditions determined with a UV radiometers. (29th March 2014) - Serrano, D.; Núñez, M.; Utrillas, M. P.; Marín, M. J.; Marcos, C.; Martínez‐Lozano, J. A.
ABSTRACT Using a sky camera, episodes characterized by overcast low clouds in the Valencia region of Spain have been selected for analysis. One year of cloud optical depth data have been produced by inverting UV erythemal irradiance measured with a UVB‐1 radiometer from Yankee Environmental Systems using the LibRadtran radiative transfer model. Measurement uncertainties, aerosol single scattering albedo and cloud properties are, in order of decreasing importance, the most important factors influencing the accuracy of cloud optical depth retrieval when using UV erythemal radiometers. Statistics for cloud optical depth show a highly skewed frequency distribution best described by a gamma distribution with highest frequency between optical depths of 10 and 15 and optical depths exceeding 100 at the extreme high end.